Primate Stefan Wyszyński’s Pro Memoria Journal as a Historical Source - Łatka, Rafał (Kwartalnik Historyczny, 2023)
This article is a concise analysis of the value of Primate Stefan Wyszyński’s Pro memoria as a historical source. It presents the most important facts concerning the hierarch’s journal, and proceeds to present a comprehensive discussion of the topics which Wyszyński touched upon in his notes, and of his writing style. The summary indicates fields of research which could utilize Pro memoria to their benefit, and also recapitulates the potential importance of the journal for scholarly research into the history of Poland in the years 1949–81.